Internationalization and imprints of the pandemic on higher education worldwide - Wiseman, Alexander W. 1968-; Matherly, Cheryl; Crumley-Effinger, Max (Emerald Publishing, 2023)
The pandemic forced significant changes to institutional and individual academic activities and norms, while highlighting inequities, opportunities, and challenges already present in the realm of internationalization in its plurality around the globe. Internationalization and Imprints of the Pandemic on Higher Education Worldwide chronicles such changes and issues, but also empirically forecasts their impacts on the ways in which internationalization at the post-secondary level has responded in practice to new realities, exigencies, and possibilities. The chapter authors address three key areas: higher education leadership and policy in times of crisis, international mobility and student experiences modified by Covid-19, and the mobilization and acceleration of learning technologies in response to Covid-19. This timely collection addresses contemporary issues and the future trajectories in International Education, essential reading for policymakers and educational researchers.
Keywords: Transnational education; Education, Higher; COVID-19 Pandemic, 2020- / Social aspects; Education, Schools, Levels; Higher; Higher & further education, tertiary education